2011
DOI: 10.4315/0362-028x.jfp-10-429
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Free Chlorine Concentrations Needed To Prevent Escherichia coli O157:H7 Cross-Contamination during Fresh-Cut Produce Wash

Abstract: This study was conducted to investigate the effect of free chlorine concentrations in wash water on Escherichia coli O157:H7 reduction, survival, and transference during washing of fresh-cut lettuce. The effectiveness of rewashing for inactivation of E. coli O157:H7 on newly cross-contaminated produce previously washed with solutions containing an insufficient amount of chlorine also was assessed. Results indicate that solutions containing a minimum of 0.5 mg/liter free chlorine were effective for inactivating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
109
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(119 citation statements)
references
References 25 publications
9
109
0
1
Order By: Relevance
“…The apparent ineffectiveness of both chlorine treatments at higher concentrations and longer treatment times may be attributed to the protection rendered by the microtopography of the vegetables; microorganisms can find protection in plant tissues such as stomata, crevices, and cuts, and even in self-assembled biofilms (Stevens, 1982;Durak et al, 2012;Lin et al, 2002;López-Gálvez et al, 2009;Luo et al, 2011;Morris et al, 1997;Seo and Frank 1999;Takeuchi and Frank, 2001;Takeuchi et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent ineffectiveness of both chlorine treatments at higher concentrations and longer treatment times may be attributed to the protection rendered by the microtopography of the vegetables; microorganisms can find protection in plant tissues such as stomata, crevices, and cuts, and even in self-assembled biofilms (Stevens, 1982;Durak et al, 2012;Lin et al, 2002;López-Gálvez et al, 2009;Luo et al, 2011;Morris et al, 1997;Seo and Frank 1999;Takeuchi and Frank, 2001;Takeuchi et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Sodium hypochlorite loses its effectiveness on reacting with organic compounds (Inatsu et al, 2005b;Rodgers et al, 2004;Warriner et al, 2003). After using it to wash fresh-cut lettuce inoculated with a high organic load, Baert In addition, Luo et al (2011) explained that when the initial chlorine concentration is low, most chlorine present in the wash solution is consumed in such reactions, leaving little or none for disinfection. The factors responsible for reducing the bactericidal effect of chlorine during vegetable washing includes vegetable type and wash water ratio, the amount of surface organic matter, vegetable preparation (e.g., shredded or pieces), and inoculation methods (Kondo et al, 2006;Beuchat, 1999;Beuchat et al, 2004;Francis and O'Beirne, 2004;Lang et al, 2004;Nthenge et al, 2007;Singh et al, 2002).…”
Section: Effect Of Sanitizer Solution Reuse On Free Chlorine Concentrmentioning
confidence: 99%
“…This highlights an additional advantage of NEOW in fresh-cut salad sanitizing procedures, because this type of product processing releases copious amounts of vegetable "juice" into the washing water, drastically increasing the water organic load. Such high organic load in the water may also lead to an increased formation of toxic chlorine byproducts and generation of chlorine gas (Luo et al, 2011). Since the NEOW technique enables a tighter control of free chlorine concentrations, it contributes for the minimization of toxic organochlorinated by-product formation.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors also reported that a small concentration of NEOW (50 mg L −1 free chlorine) was as effective as 120 mg L −1 of chlorine from NaOCl in the reduction of the total aerobic mesophilic count in the minimal processed vegetables washed. Industrially, traditional chlorine-based decontamination procedures include 50-200 ppm free chlorine in a vast majority of minimally processed product manufacturers (Luo et al, 2011) with a contact time of 1-2 min (Beuchat et al, 1998). At the industrial plant studied in this work, sodium hypochlorite is regularly used up to a maximum concentration of 90 ppm of free chlorine.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the capacity of hypochlorous acid to reduce the viable microbial bioburden and to prevent cross-contamination, it is also used as a sanitizer during equipment cleaning. Its overall minimal impact on nutritional and esthetic qualities of the produce, its well-known capability to inactivate pathogens in suspensions, and its low cost contribute to its common usage (19). Maintaining free chlorine in washing solutions with fresh-cut produce is challenging because fresh-cut products release copious amounts of juice into the wash water.…”
mentioning
confidence: 99%